The law and practice of the United Nations - Conforti, Benedetto (Legal aspects of international organization ;, 2010)
This fully up-dated, third revised edition of Conforti's thought-provoking and challenging textbook, The Law and Practice of the United Nations, provides a comprehensive legal analysis of problems concerning membership, the structure of UN organs, their functions and their acts, taking into consideration the text of the Charter, its historical origins, and, particularly, the practice of the organs. Its main focus is on the practice of the Security Council. In particular the action of the Security Council under Chapter VII has been taken into account. The legal literature on Chapter VII - a lit.